Gambaran Pengetahuan tentang Dismenorhea dan Penanganannya pada Mahasiswi Program Studi Sarjana Kedokteran Angkatan 2022 di Universitas Kristen Krida Wacana pada bulan Oktober Tahun 2024 - Kurniawan, Melania Oudinne; Irmansyah, Frizar; Goenawan, Adrian (Jurnal MedScientiae, 2025)
Background: Dysmenorrhea is one of the most common gynecological problems that occurs in all menstruating patients. The prevalence of dysmenorrhea can vary between 16% and 91% in individuals of reproductive age. According to statistics from the World Health Organization (WHO), there are around 1.769.425 women (90%) who experience dysmenorrhea, with 10-15% of them experiencing severe dysmenorrhea. In Indonesia, the number of dysmenorrhea cases reached 107.673 people (64,25%), which included 59.671 people (54,89%) with primary dysmenorrhea and 9.496 people (9,36%) with secondary dysmenorrhea. Objective: to find out knowledge about dysmenorrhea and its treatment among students of the 2022 Undergraduate Medical Study Program in treating dysmenorrhea at Krida Wacana Christian University in October 2024. Method: This research is a categorical descriptive study at Campus II of Krida Wacana Christian University. Determining the sample size using a non-probability sampling technique, purposive sampling type, with a sample size of 97 samples. The data was processed using the SPSS 29 statistical program. Results: the results of research conducted on students of the 2022 Undergraduate Medical Study Program at Krida Wacana Christian University totaling 103 respondents, it was obtained that 13 respondents (12.6%) had good knowledge, 89 respondents were obtained (86.4%), and less than 1 person (1.0%). Conclusion: In this study, it was found that the majority of respondents had sufficient knowledge, 89 people (86.4%).